Principles of modern genetics - Elseth, Gerald D. (West Pub. Co., 1995)
This text , for a one-semester general genetics course for science majors, integrates the molecular and classical (Mendelian) approaches to genetics and takes an analytical approach, emphasizing problem solving and the analysis of research data.